2021
DOI: 10.18517/ijaseit.11.3.15350
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Big Data-Based Potential Applications in Marine Shipping Management

Abstract: Shipping is becoming a spearhead economic sector in sea countries. Over 90% of goods and raw materials are transported globally by marine shipping. However, the requests from the advanced transport ship generations include much more modern facilities, larger cargo space, faster moving, and flexible controlling cargo from inland with a shorter time. As a result, the demand for digitalization of maritime is increasing in a flexible virtual environment and under pressure to reduce costs. Big Data plays an extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Based on internationalization and diversification, the fourth-generation ports were born with a network system for enhancing the connectivity between ports in the region. This system allowed many seaports to connect and incorporate to develop the seaport system in a country and larger areas [69][70][71] Network ports were the name given to this system. As part of a worldwide transport logistics network, these ports worked hand in hand with other logistics companies operating in numerous different geographic regions.…”
Section: Seaportmentioning
confidence: 99%
“…Based on internationalization and diversification, the fourth-generation ports were born with a network system for enhancing the connectivity between ports in the region. This system allowed many seaports to connect and incorporate to develop the seaport system in a country and larger areas [69][70][71] Network ports were the name given to this system. As part of a worldwide transport logistics network, these ports worked hand in hand with other logistics companies operating in numerous different geographic regions.…”
Section: Seaportmentioning
confidence: 99%
“…This study established how big data can be used to analyze both conventional and unconventional data to generate revenue [41]. This study showed that big data is a new technology that must be implemented to relieve the marketing strategy in outbound campaigns, reconfigure the deal plan to make it more effective [14], and has a significant impact on management and technology as well as give a wider impact on the industry's preparedness [13].…”
Section: Figure 5 Rating Affected By Productmentioning
confidence: 99%
“…Thus, big data plays a crucial role in determining which traditional and non-traditional data can generate profits [13]. Big data is a new technology that must be used to improve the deal plan's efficiency and support the branding strategy in outbound efforts [14]. The implementation of big data analysis, on the other hand, necessitates the use of effective interactive data visualization software that offers a complete image and has quick performance, scalability, and processing time.…”
Section: Introductionmentioning
confidence: 99%
“…In modern supply chain management, one of the most critical components is the integration of operations involving the maritime and logistics sectors [37], [38]. Ports are essential nodes in the global logistics network, serving as hubs that facilitate the movement of goods between different modes of transportation, including ships, trucks, and trains, among others [39], [40]. Efficient port operations are essential for reducing the time it takes for goods to travel, saving money, and enhancing the overall efficiency of supply chain activities [41] [42].…”
Section: Introductionmentioning
confidence: 99%